ANALISA KRITIS KONSEP MANAJEMEN RESIKO DALAM PERSPEKTIF ISLAM - Royani, Ahmad (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
The concept of uncertainty in Islamic economics is one of the important pillar in Islamic risk management. Naturally, in business activities in this world no one wants a business or investment to suffer losser. Risk management is a logical method and systematically identification, qualifies, determines attitudes, sets solutions, monitors, reporting risks in every actifity and process. Risk management includes three main things, namely risk identification, evaluation and risk measurement, and the third risk management. The company’s prudence in responding to risk is an effort to maximize the steps to manage risk properly and in essence these risk can bring profit.